2008
DOI: 10.1016/j.anbehav.2007.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent signalling success in the wolf spider, Schizocosa retrorsa

Abstract: Understanding past as well as present selection pressures that have influenced the origin, evolution and maintenance of existing communication systems presents a considerable challenge to biologists. Among the multitude of factors known to influence signal form, characteristics of the signalling environment play a crucial role. For example, numerous empirical studies have demonstrated a clear effect of signalling habitat on visual signal evolution in fish (Endler, 1991; Endler, 1992; Boughman, 2001; Maan et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 66 publications
(21 reference statements)
3
45
1
1
Order By: Relevance
“…Schizocosa retrorsa, in contrast, is found mainly on pine litter, red clay, or sand and produces seismic signals via pedipalpal drumming. The seismic signaling substrate is also known to influence copulation success in S. retrorsa as pairs are more likely to copulate on their natural substrates of pine litter and red clay as compared with leaf litter (Hebets, Elias, et al 2008). Although the emerging pattern suggests that the signaling environment has played a major role in shaping courtship form and function for at least some Schizocosa species, with currently available data, we are not yet able to fully elucidate the links between natural signaling substrate, seismic signal production, and seismic signal importance or function across Schizocosa species.…”
Section: Discussionmentioning
confidence: 99%
“…Schizocosa retrorsa, in contrast, is found mainly on pine litter, red clay, or sand and produces seismic signals via pedipalpal drumming. The seismic signaling substrate is also known to influence copulation success in S. retrorsa as pairs are more likely to copulate on their natural substrates of pine litter and red clay as compared with leaf litter (Hebets, Elias, et al 2008). Although the emerging pattern suggests that the signaling environment has played a major role in shaping courtship form and function for at least some Schizocosa species, with currently available data, we are not yet able to fully elucidate the links between natural signaling substrate, seismic signal production, and seismic signal importance or function across Schizocosa species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no relationship was found between vibratory signal complexity and vibratory signal importance and the vibratory signals were hypothesized to be selected for signal efficacy. Indeed, studies on both jumping spiders (Elias et al, 2004) and wolf spiders (Hebets et al, 2008) have demonstrated that the spectral characteristics of the vibratory signal components correspond to low signal attenuation on substrate-types characteristic of their natural signaling environment (e.g. leaf litter), suggesting selection for signal efficacy.…”
Section: Selection For Signal Complexity In Cursorial Spidersmentioning
confidence: 99%
“…With the advent of non-contact methods of recording vibrations, such as laser vibrometry, the field has made substantial advances in recent years (e.g. Landolfa and Barth, 1996;Elias et al, 2006;Hebets et al, 2008;Wignall and Herberstein, 2013a).…”
Section: Signal Complexity In Web-building Spidersmentioning
confidence: 99%
“…Substrate choice can be related to communication and copulation success (e.g. wolf spiders; Hebets et al 2008). Animals make substrate choices as part of antipredator behaviours such as hiding and shoaling (e.g.…”
Section: Introductionmentioning
confidence: 99%